ANALISIS TEKNIS DAN EKONOMIS OPTIMALISASI SISTEM PENGERUKAN HIDROLIK MENGGUNAKAN CUTTER SUCTION DREDGER DAN BOOSTER PUMP PADA BENDUNGAN TANGGA DAN SIGURA-GURA - Mahendra Sitinjak; Suselo Utoyo; Ayisya Cindy Harifa (Jurusan Teknik Sipil Politeknik Negeri Malang, 2025)
Sediment accumulation in the Tangga and Sigura-Gura Dams, which are integral parts of the Asahan River hydropower generation system, has significantly reduced their effective reservoir capacity. This issue disrupts operational efficiency and increases the risk of infrastructure damage. This study aims to conduct a technical and economic analysis of three hydraulic dredging system configurations using a Cutter Suction Dredger (CSD) combined with Floating Booster Pumps and a land-based booster pump, in order to determine the most optimal system for sediment removal. Technical evaluation was conducted using the Darcy–Weisbach equation to assess energy loss (head loss), along with a cavitation risk analysis based on the Net Positive Suction Head (NPSH) parameter. Cost analysis referred to the 2025 Unit Price Analysis (AHSP) published by the Indonesian Ministry of Public Works. The results indicate that the configuration comprising 1 CSD unit, 1 submersible pump, 2 floating booster pumps in parallel, and 1 land-based booster pump is the most efficient system. It delivers a slurry flow rate of 600 m³/hour, a total head loss of 72.7 meters, and completes the dredging process within 3 months at a unit cost of Rp147,202.47/m³. Therefore, this configuration is considered technically and economically optimal, and supports the long-term sustainability of hydropower generation operations in the upstream area of the Asahan River.